Congenital Malaria in a 2-Day-Old Neonate: A Case Report and Literature Review - Dickson Kajoba; Walufu Ivan Egesa; Habonimana Jean Petit; Muhiadin Omar Matan; Goretty Laker; William Mugowa Waibi; Daniel Asiimwe (Case Reports in Infectious Diseases)
Congenital malaria is the presence of malaria parasites in a blood smear obtained from a neonate usually within 24 hours to 7 days of life. It has for long been regarded a rare condition. However, recent data indicate that congenital malaria complicates around 35.9% of live births globally, 0–37% in Sub-Saharan Africa and about 4–6.1% in Eastern Uganda. We present a 2-day-old neonate who presented with fever, irritability, and failure to breastfeed. Laboratory tests indicated that the neonate had a positive Giemsa-stained peripheral smear for Plasmodium falciparum, with a positive malaria rapid diagnostic test (MRDT) for P. falciparum malaria. The mother had a negative peripheral film for malaria and a negative MRDT. The neonate was managed with intravenous artesunate with improvement.